Effect of Glycine Dopant on FTIR Spectrum of Ammonium Dihydrogen Phosphate (ADP) Crystal Grown by Slow Evaporation, Rotation and SR Methods - Khan, A. Z.; Khan, Z. S. (New Trends in Physical Science Research Vol. 6, 2022)
Diverse molar concentrations of Ammonium Dihydrogen Phosphate crystals doped with Glycine (GADP) have been generated using different processes, including slow evaporation, rotation, and Sankaranarayanan - Ramasamy (SR) procedures. ADP crystals have found many applications in Non-linear optics, electro-optics, and transducer devices. On the developed GADP crystals, the Fourier Transform Infrared (FTIR) researches have been widely examined. The extra peaks in the FTIR spectrum that correspond to the functional groups of Glycine reveal the interaction between ADP and the dopant. The presence of all functional groups in the substance is confirmed by FTIR's standard spectrum statistics. When compared to the conventional slow evaporation method created Glycine doped ADP crystals, the spectra for ADP crystals doped with Glycine grown by Rotation and SR procedures had identical peaks with minimal variance.